PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN PADA PT. ISHIKAWAJIMA HEAVY INDUSTRIES (IHI) POWER SERVICE INDONESIA - Agustin, Farida; Supriyadi, Supriyadi; Dwi Andrarini, Nova (DESANTA (Indonesian of Interdisciplinary Journal), 2025)
This research aims to determine the influence of the transformational leadership style on employee performance at PT. Ishikawajima Heavy Industries (IHI) Power Service Indonesia, to determine the influence of interpersonal communication on employee performance at PT. Ishikawajima Heavy Industries (IHI) Power Service Indonesia, and to determine the influence of the transformational leadership style and interpersonal communication on employee performance at PT. Ishikawajima Heavy Industries (IHI) Power Service Indonesia. In this research, data was taken from a total sample of 119 respondents by distributing a Google Form questionnaire for 2 weeks at PT. Ishikawajima Heavy Industries (IHI) Power Service Indonesia. Then the data was processed using SPSS (Statistical Package for Social Science) software version 26 through descriptive statistical tests, validity tests, reliability tests, linear regression tests, classical assumption tests, and hypothesis tests. Hypothesis test results show that the Transformational Leadership Style (X1) obtained a calculated t value of 2.116 > t table, namely 1.98063, and a sig value of 0.036 < 0.05; then H1 was accepted and H0 was rejected. The Interpersonal Communication variable (X2) obtained a calculated t value of 3.901 > t table, namely 1.98063, and a sig value of 0.000 < 0.05; then H2 was accepted and H0 was rejected. And the variables Transformational Leadership Style (X1) and Interpersonal Communication (X2) have a calculated F value of 20,470 > F table, namely 3.16, and a sig value of 0.000 < 0.05.